1999
DOI: 10.23986/afsci.5632
|View full text |Cite
|
Sign up to set email alerts
|

HPLC analysis of vitamin B6 in foods

Abstract: The objective of this work was to evaluate the methods for determination of vitamin B6 in foods. To achieve this, the literature review focused on sample treatment and liquid chromatographic analysis of vitamin B6 related compounds. In the experimental part, the chosen sample pretreatment and the high-performance liquid chromatographic (HPLC) method were validated, and used to produce vitamin B6 data on various food items commonly consumed in Finland. The main emphasis of the sample treatment was on the extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 157 publications
(272 reference statements)
0
10
0
Order By: Relevance
“…The current model for the salvage pathway is derived from studies in E. coli, which produces PNP de novo. It is possible that plants, which produce PLP de novo but produce PN as the predominant vitamer (Ollilainen 1999), have an alternate means of PN synthesis not found in E. coli, perhaps directly from PLP rather than via dephosphorylation of PLP followed by PL reduction. Further research is needed to understand the complexity of the salvage pathway in plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current model for the salvage pathway is derived from studies in E. coli, which produces PNP de novo. It is possible that plants, which produce PLP de novo but produce PN as the predominant vitamer (Ollilainen 1999), have an alternate means of PN synthesis not found in E. coli, perhaps directly from PLP rather than via dephosphorylation of PLP followed by PL reduction. Further research is needed to understand the complexity of the salvage pathway in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Since PLP is the active cofactor, most studies have focused on its production from the other vitamers and comparatively little is known about reactions that convert PL or PLP to the other vitamers. In a study of B6 vitamer content in food, Ollilainen found that the major vitamer present in plant-derived foods is usually PN, either free or glycosylated (Ollilainen 1999). Thus plants must have an efficient system for producing PN.…”
Section: Introductionmentioning
confidence: 99%
“…The bioavailability of vitamin B6 derived from plant food sources is also an important factor influencing adequate intake ( Figure 1 ). Plants contain multiple B6 vitamers and a substantial fraction of vitamin B6 is present as pyridoxine-5 ′ -β- D -glucoside (PN-glucoside; Gregory and Ink, 1987; Ollilainen, 1999; Figure 1 ). While PN, PL, and PM and their phosphorylated derivatives are fully bioavailable from plant food, PN-glucoside is only 50% bioavailable (Gregory, 2012; Figure 1 ).…”
Section: Main Sourcesmentioning
confidence: 99%
“…3g-i) because the molar absorptivity of the complex is lower than that of pyridoxine under alkaline conditions. [20] Additionally, the absorption peak experienced a blue shift at the higher pH. In the neutral range, the form of free pyridoxine is different from that in the complex (Fig.…”
mentioning
confidence: 94%